استراتيجيات إدارة الضغوط المهنية كمدخل لتفعيل الإدارة المدرسية الحديثة: قـراءة تحليلية - حرايرية, عتيقة (University of Eloued جامعة الوادي, 2019)
ملخص تؤكد نتائج العديد من الدراسات أن الضغوط المهنية (أو ضغوط العمل) هي واحدة من أهم معوقات تحقيق الأهداف في المنظمات الحديثة، لأن أي خلل قد يصيب الإنسان نتيجة لضغوط العمل سينعكس بشكل مباشر على أداء المنظمة وعلى قدرتها على التكيف مع الظروف البيئية المتغيرة وضمان بقائها واستمرارها، وتزداد أهمية هذا طرح إذا تعلق الأمر بالمدرسة بإعتبارها منظمة اجتماعية وجدت لتحقيق أهداف مرتبطة بإشباع احتياجات معينة في المجتمع. في إطار هذا الطرح، سنحاول مناقشة وتحليل الاستراتيجيات المتاحة لإدارة الضغوط المهنية كمدخل لتفعيل الإدارة المدرسية الحديثة من أجل زيادة قدرة هذه التنظيمات على تحقيق أهدافها بكفاءة وفعالية عن طريق الاستثمار في قدرات الأفراد نحو تقديم أفضل أداء ممكن عن طريق تزويد الأفراد والمنظمات بالآليات الممكنة لإدارة هذه الضغوط. Abstract The results of several studies confirm that work pressures are one of the most important obstacles to achieving the objectives in modern organizations. because any malfunction that may affect human beings as a result of work pressures will directly affect the performance of the organization and its ability to adapt to changing environmental conditions and ensure their survival and continuity, This is even more important when it comes to school as a social organization found to achieve goals related to meeting certain needs in society. In this context, we will attempt to discuss and analyze the strategies available to manage professional pressures, as an input to modern school management in order to increase the ability of these organizations to achieve their objectives efficiently, and effectively by investing in the ability of individuals to provide the best possible performance by providing individuals and organizations with possible mechanisms to manage these pressures
Strategies of managing professional pressures as an input to activate modern school administration: analytical reading
مجلة الدراسات والبحوث الاجتماعية المجلد 07 العدد 02 جامعة الوادي
Keywords: الضغوط المهنية، إدارة الضغوط المهنية، بيئة العمل، الإدارة المدرسية الحديثة; Work Pressures, Work Pressures Management, Work Environment, Modern School Management